EVALUATION OF PHYLLANTHUS EMBLICA EXTRACT AS ANTIBACTERIAL AND ANTIBIOFILM AGAINST BIOFILM FORMATION BACTERIA - & Hamzah, AL-Gbouri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study was to evaluate the antibacterial effect of Phyllanthus emblica extract by (ethanol: methanol 1:1) against Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli at different concentration started with 20, 10, 5, 2.5, 1.25 and 0.625 mg/ml. The antibacterial activity was determined by the agar well diffusion method to investigate the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The alcoholic extract of Phyllanthus emblica had the highest antibacterial activity at 20 mg/mL and 5 mg/mL except in Pseudomonas aeruginosa where the value of inhibition was between 20 mg/mL and 10 mg/mL whereas The MIC concentrations were mostly very high and ranged from 5 to 1.25mg/ml while MBC range from 10 to 2.5 mg/ml against tested bacteria. In this study, we evaluated the effect of Phyllanthus emblica against Pseudomonas aeruginosa biofilm formation was evaluated and the biofilm inhibitory concentrations of the Phyllanthus emblica extract was 40-6.25mg/ml.This implies that they may contain valuable substances for application directed against pathogenic biofilms. The use of herbal extract such as Phyllanthus emblica represent a new date for antimicrobial therapy after increasing the antibiotic resistance to microbes.